TV family values : gender, domestic labor, and 1980s sitcoms - Leppert, Alice (Rutgers University Press, 2019)
During the 1980s, U.S. television experienced a reinvigoration of the family sitcom genre. This book focuses on the impact the decade's television shows had on middle class family structure. These sitcoms sought to appeal to upwardly mobile "career women" and were often structured around non-nuclear families and the reorganization of housework. Drawing on Foucauldian and feminist theories, the author examines the nature of sitcoms such as Full House, Family Ties, Growing Pains, The Cosby Show, and Who's the Boss? against the backdrop of a time period generally remembered as socially conservative and obsessed with traditional family values